Controllability of magnetorheological shock absorber: I. Insights, modeling and simulation*Part of work was done while Xian-Xu 'Frank' Bai was a joint PhD student of Chongqing University and University of Maryland, College Park. (6th December 2018) - Bai, Xian-Xu; Shen, Sheng; Wereley, Norman M; Wang, Dai-Hua
Abstract: The smart fluids—magnetorheological (MR) fluids show the potentials for high-speed shock mitigation applications because of their fast response and large controllable damping range. In order to match the high-speed applications of MR fluids, the structural design and controllability evaluation of MR actuators are of great significance. Controllability of MR actuators are defined to be evaluated by the mechanical behaviors (i.e. damping force controllability), including the controllable damping force range, dynamic range and constant stroking load velocity range, and response time performance (i.e. real-time controllability). We proposed an internal bypass MR shock absorber (MRSA) (Bai et al 2013a IEEE Trans. Mag. 49 3422–5), which presents the possibility in vibration control and shock mitigation applications. In the internal bypass MRSA, the gap formed by the coaxially assembled inner and outer cylinders is the flow channel for MR fluids. The electromagnetic coil windings evenly wound on the outer wall of the inner cylinder and the active rings contribute to the MR effect, and continuous adjustable damping is realized through applying current into the electromagnetic coil windings. In Part I of this paper, the principle and the mechanical behaviors of the internal bypass MRSA is further in-deeply investigated via theoretical modeling and simulations. Based on the fluid dynamics—parallel plate models and the finite element analysis software ANSYS/Fluent, the mathematical model and the fluidic entities of the internal bypass MRSA are established, respectively. Response time model of the internal bypass MRSA under a voltage driver is established. The static magnetic field distributions of the internal bypass MRSA under different current excitations are obtained via ANSYS/Workbench. The response times of the internal bypass MRSA under transient impulse current excitation and transient impulse voltage excitation are obtained by transient electromagnetic simulation. The damping force performance of the conventional unicoil MRSA with an electromagnetic coil winding in positon, multicoil MRSA with five electromagnetic coil windings in positon and the internal bypass MRSA are compared and analyzed. As compared with the conventional unicoil and multicoil MRSAs with coupled structures of the piston and the electromagnetic coil windings, the internal bypass MRSA with decoupled arrangement shows much better damping force controllability. Experimental test and controllability evaluation of the internal bypass MRSA will be conducted and presented in Part II of this paper.